Facial Artery Musculomucosal Flap Operative Techniques. Issue 3 (23rd February 2022) - Rabbani, Cyrus C.; Lee, Andrew H.; Desai, Shaun C.
Abstract : Summary: Regional flaps are an important component of the reconstructive ladder and represent a versatile option in reconstructing various oral cavity defects. An axial buccal flap based on the facial artery, the facial artery musculomucosal flap, was first described by Pribaz et al. and has been shown to have good functional outcomes with minimal morbidity. Indeed, other surgeons have praised its favorable arc of rotation, reliability, and role as an alternative to free tissue transfer, with shorter duration of general anesthesia and allowance for earlier postoperative mobilization. The facial artery musculomucosal flap has significant versatility, as it can be superiorly or inferiorly based and can be performed in either single- or two-stage fashion. It is of particular advantage for reconstruction of the oral cavity (retromolar trigone, hard palate, alveolar ridge, lip, tongue, and floor of mouth), oropharynx (tongue base, lateral pharynx, and soft palate), and sinonasal structures. Despite its advantages, its widespread use has been limited by a lack of familiarity and difficulty in safely raising a reliable flap consistently. The senior author (S.C.D.) has successfully utilized a high volume of facial artery musculomucosal flaps with a low complication rate in a broad array of oral cavity and oropharyngeal defects. In this article, the authors share technical details on how to harvest and inset this flap by incorporating key landmarks in a reliable fashion.